Geochemical Properties of Fire Opal Occurences in Kütahya (SW Turkey) - TEKBAS CANDAR*, M.; ISLER†, F. (Asian Journal of Chemistry, 2024)
The Simav fire opal occurences have specific characteristics. It has a variety of appearance micro and nanostructures. Chemical, mineralogical properties, optical observation and SEM analyses of Simav fire opal occurences have been investigated. Micromorphology, crystal structure, particle size were examined. To purpose scanning electron microscopes used on microtextures on fire opal. The yellow to brown colour is correlated with Fe concentration. The purpose of the peresent investigations are two fold (1) clarify the microtextures at a level of nanometer scale (2) to analyze the mechanism of their formation.